TRANSFER TEKNOLOGI PENGOLAHAN TAUCO SEBAGAI BAHAN PENYEDAP MAKANAN KAYA ASAM AMINO - A.S, Duniaji; Tuninggrat, I A Mahatma (Buletin Udayana Mengabdi; Vol 10 No 2 (2011): Volume 10 No.2 – September 2011, 2012)
Tauco” is one of the food Ingredients made from fermented soybean process (Buckle, dkk., 1986). “Tauco” has been produced and distributed in whole markets and it is very popular as a traditional fermented food in Indonesian. “Tauco” consists of several amino acids such as arginine, sodium glutamic, lysine and glutamic acid. Glutamic acid and their salt derivates lead to contribute a typical flavor in “Tauco”. “Tauco” is produced well in Jawa and marketed to the traditional markets and supermarket in Bali. This program aimed to technology transfer of tauco processing as a food ingredient and introduce on how to improve the quality of tauco as traditional fermented in facing the global market competitions. Hence, we are a group of lecturers of Faculty of Agricultural Technology Udayana University held on dissemination of Tauco processing to the Mambal village societies in order to improve their skill and technology. Tauco can be made with a simple equipments and methods. The method of Tauco processing beginning from preparing good quality of soybean and soaked for 24 hours. Soaked soybean is continued to be boiled, cooked and then cooled. Ragi tempe was inoculated and spread on the surface of cooked soybean and fermented for 3-4 days. Soybean fermentation is continued to be soaked in 20 percent brine solute for 5-7 days. Finally, soybean pasta is to be pasteurized for 30 seconds with adding some spices and be bottled